Multicriteria sustainability evaluation of thirteen extensive rearing and full-cycle family livestock farming systems of Uruguay - Febrer, Carla; Dieguez, Francisco; Gazzano, Inés (Agrociencia Uruguay, 2021)
In the context of agrarian intensification and unsustainability of family livestock farming in Uruguay, it is important to understand the critical elements of productive units to guide possible improvement strategies. This study integrates socioeconomic and environmental information collected through a system of records of the project “Improvements in Family Livestock Farming Sustainability in Uruguay” (inia, mgap and the Agricultural Plan Institute). The system evaluated, interpreted and identified critical points for extensive family farming systems. This study presents the constructions of a multicriteria approach of sustainability indicators incorporating environmental, social and productive aspects to evaluate 13 Uruguayan family livestock systems. The results show low relative values in the indicators of the environmental dimension, allowing to direct possible changes in the practices of the productive system. On the other hand, with this case study, the importance of considering a multidimensional vision in the analysis of production systems is evident in order to contemplate all their complexity and identify the critical aspects to take into account.